Design and methodology of the SARCopenia trajectories and associations with adverse clinical outcomes in patients on HemoDialysis: the SARC-HD study - Duarte, Marvery P.; Pereira, Marina S.; Baião, Victor M.; Vieira, Fábio A.; Silva, Maryanne Zilli Canedo [UNESP]; Krug, Rodrigo R.; Inda-Filho, Antônio J.; Ferreira, Aparecido P.; Lima, Ricardo M.; Avesani, Carla Maria; Nóbrega, Otávio T.; Reboredo, Maycon M.; et al. (Springer Nature, 2023)
Background: Sarcopenia has been associated with adverse outcomes in patients with chronic kidney disease (CKD), particularly in those undergoing hemodialysis (HD). However, the trajectories across sarcopenia stages, their determinants, and associations with adverse clinical outcomes have yet to be comprehensively examined. Methods: The SARC-HD is a multicenter, observational prospective cohort study designed to comprehensively investigate sarcopenia in patients on HD. Eligibility criteria include adult patients undergoing HD for ≥ 3 months. The primary objective is to investigate the trajectories of sarcopenia stages and their potential determinants. Secondary objectives include evaluating the association between sarcopenia and adverse clinical outcomes (i.e., falls, hospitalization, and mortality). Sarcopenia risk will be assessed by the SARC-F and SARC-CalF questionnaire. Sarcopenia traits (i.e., low muscle strength, low muscle mass, and low physical performance) will be defined according to the revised European Working Group on Sarcopenia in Older People and will be assessed at baseline and after 12 follow-up months. Patients will be followed-up at 3 monthly intervals for adverse clinical outcomes during 24 months. Discussion: Collectively, we expect to provide relevant clinical findings for healthcare professionals from nephrology on the association between sarcopenia screening tools (i.e., SARC-F and SARC-CalF) with objective sarcopenia measurements, as well as to investigate predictors of trajectories across sarcopenia stages, and the impact of sarcopenia on adverse clinical outcomes. Hence, our ambition is that the data acquired from SARC-HD study will provide novel and valuable evidence to support an adequate screening and management of sarcopenia in patients on HD.
Keywords: Chronic kidney disease; Dialysis; Physical function; SARC-F; Sarcopenia